2021
DOI: 10.3390/app11020675
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects of Designing Modular PEMFC Stacks as Power Sources for Unmanned Aerial Vehicles

Abstract: Two types of air-cooled modular polymer membrane fuel cells (PEMFC) stacks with full equipment were constructed and investigated as components of hybrid power sources. The first, a 2-kW PEMFC stack, was assembled from two 1-kW PEMFC modules electrically connected in parallel and compared with a commercial PEMFC stack built from one 2-kW PEMFC module. The second, a 500-W PEMFC stack, was assembled with three modules connected in parallel. It was found that the two-module PEMFC stack was capable of operation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It has been studied and reported that utilization of hydrogen fuel cell vehicles has been pointed in the United States and 5,899 hydrogen vehicles developed for commercialization (Bayrak et al, 2020). For the promotion of hydrogen utilized vehicles, companies like Toyota Mirai, Honda Clarity, Renault-Nissan, General Motors and Honda have formed alliances for the joint production (Giacoppo et al, 2017;Dudek et al, 2021).…”
Section: Hydrogen Vehiclesmentioning
confidence: 99%
“…It has been studied and reported that utilization of hydrogen fuel cell vehicles has been pointed in the United States and 5,899 hydrogen vehicles developed for commercialization (Bayrak et al, 2020). For the promotion of hydrogen utilized vehicles, companies like Toyota Mirai, Honda Clarity, Renault-Nissan, General Motors and Honda have formed alliances for the joint production (Giacoppo et al, 2017;Dudek et al, 2021).…”
Section: Hydrogen Vehiclesmentioning
confidence: 99%
“…This group includes proton exchange polymer membrane fuel cells (PEMFCs), which can operate in the temperature range from 20 to 70  C (LT-PEMFC), and solutions operating at temperatures of 120-160  C (HT-PEMFC) [4,31]. It should be noted that LT-PEMFC polymer cells, with respect to HT-PEMFCs, have already been used commercially in transportation for many years [5,6,31].…”
Section: Introductionmentioning
confidence: 99%
“…From the beginning of the 1970s to today, microcontrollers and microcomputers have evolved very quickly. Nowadays, most embedded systems created based on microcontrollers are used in many applications including industrial [5,21], consumer [33], commercial [3], automotive [13], medical [12,18], home appliances [17,31], telecommunications [2], spacecraft [14], military applications [8,15], and so forth. The total-global microcontrollers market was estimated to be USD 86.5 billion in 2020 and predicted to reach USD 116.2 billion by 2025 [4].…”
Section: Introductionmentioning
confidence: 99%